Comic book confidential mit Lynda Barry, Charles Burnes, Stan Lee, Robert Crumb, Will Eisner, Al Feldstein, Sue Coe, u.a. - Fresco, Robert 1943- (Ed. Salzgeber, 2013)
Combines historical footage, interviews, animation, and live action to trace the history of comic books from 1933 to 1988. Twenty-two significant comic artists and writers are discussed: Lynda Barry, Charles Burns, Sue Coe, Robert Crumb, Will Eisner, Al Feldstein, Shary Flenniken, William M. Gaines, Bill Griffith, Jaime Hernandez, Jack Kirby, Harvey Kurtzman, Stan Lee, Paul Mavrides, Frank Miller, Victor Moscoro, Francoise Mouly, Dan O'Neill, Harvey Pekar, Gilbert Shelton, Spain, Art Spiegelman